Experimental and Predicted Viscosities of Binary Mixtures of Styrene with o-, m- or p-Xylene and Toluene at Different Temperatures - Nabi, Firdosa; Ahmad Malik, Maqsood; G. Jesudason, Christopher (Asian Journal of Chemistry, 2011)
The viscosities (h) of pure styrene, toluene, o-xylene, m-xylene or p-xylene and those of their binary mixtures with styrene as common component, covering the whole composition range at the temperatures 298.15, 303.15, 308.15 and 313.15 K have been measured. From the experimental data the deviations in viscosity (Dh), deviations in Gibbs free energy of activation (DG), deviations in entropies, (DS*) and deviations in enthalpies (DH*) of activation of viscous flow have been determined. The sign and magnitude of these parameters were found to be sensitive towards interactions prevailing in the studied systems. Further, the excess molar volumes, VE, were calculated using the viscosity data for the binary mixtures. Moreover, theoretical values of viscosities of the binary mixtures were calculated using different empirical relations and theories.